Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1038/s42003-019-0719-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation drives seasonal onset of hibernation in the 13-lined ground squirrel

Abstract: Hibernation in sciurid rodents is a dynamic phenotype timed by a circannual clock. When housed in an animal facility, 13-lined ground squirrels exhibit variation in seasonal onset of hibernation, which is not explained by environmental or biological factors. We hypothesized that genetic factors instead drive variation in timing. After increasing genome contiguity, here, we employ a genotype-by-sequencing approach to characterize genetic variation in 153 ground squirrels. Combined with datalogger records (n = 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 73 publications
(93 reference statements)
0
18
0
Order By: Relevance
“…For example, in the insect literature, clines in clock gene allele frequency underlie evolved differences in diapause induction and initiation timing, and these alleles are under selection due to climate change (Bradshaw & Holzapfel, 2001; Pruisscher et al., 2018). Similar clines in timing also exist in other taxa (Figures 4 and 6), but we do not know the extent to which they share a common mechanism (see Box 2; Fenn et al., 2009; Grabek et al., 2019; Lane et al., 2011, 2019; Zervanos et al., 2010). The mammalian literature has shown that diet during preparation may influence the magnitude and duration of maintenance phase.…”
Section: Opportunities and Outlookmentioning
confidence: 69%
See 1 more Smart Citation
“…For example, in the insect literature, clines in clock gene allele frequency underlie evolved differences in diapause induction and initiation timing, and these alleles are under selection due to climate change (Bradshaw & Holzapfel, 2001; Pruisscher et al., 2018). Similar clines in timing also exist in other taxa (Figures 4 and 6), but we do not know the extent to which they share a common mechanism (see Box 2; Fenn et al., 2009; Grabek et al., 2019; Lane et al., 2011, 2019; Zervanos et al., 2010). The mammalian literature has shown that diet during preparation may influence the magnitude and duration of maintenance phase.…”
Section: Opportunities and Outlookmentioning
confidence: 69%
“…Mammal phylogeny from (Fritz et al, 2009) and insect phylogeny from (Wiens et al, 2015). Silhouettes and licenses are from phylo pic.org (Figures 4 and 6), but we do not know the extent to which they share a common mechanism (see Box 2; Fenn et al, 2009;Grabek et al, 2019;Lane et al, 2011Lane et al, , 2019Zervanos et al, 2010).…”
Section: Opp Ortunitie S and Outlookmentioning
confidence: 99%
“…After aligning and scaffolding Chicago data, Dovetail HiC library sequences were aligned and scaffolded following the same method. We named this genome HiC_Itri_2, reflecting the assembly method and that this is the second super-assembly of SpeTri2.0 ( Grabek et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…This may prompt the animals to arouse from torpor. In other words, the increase in cytoplasmic Ca 2+ during LT may be one of the factors resulting in interbout arousal following prolonged torpor (Grabek et al, 2019). Conversely, the reduction in cytoplasmic Ca 2+ during IBA and ET could represent a reduction in futile cycling meant to reduce energy expenditure.…”
Section: Discussionmentioning
confidence: 99%